BIOECOLOGY OF SILK BERRY VARIETIES (Scientific journal of the Fergana State University, 2024)
This article studies the biological and environmental features of the Tajikistan mulberry plant, seedless mulberry varieties Sanish-41, Yuzhny, Sanish-38, Sanish-33, Sanish-39. The quantitative and qualitative indicators of the varieties in the experiment were assessed by the determination method. Among the quantitative indicators of varieties in the experiment, they take into account the number of trees per calculation (pcs.), the number of branches with leaves (kg), the mass of leaves (%), the number of leaves in pure form (kg), the mass of leaves of one tree (kg), the yield of . When determining the quality indicators of varieties in the experiment, such indicators as swelling of buds, formation of 5 leaves, closure of apical buds, and flowering time were determined. We studied the yellowing of leaves, the time of leaf fall, and the growing season (days). The area of ​​the experimental plot is 3300 m2, the soil is light gray soil, irrigated, soil fertility is average, plant varieties in the II tier, in the IV repetition, R.A. Placed according to the randomization method recommended by Fisher. In our experiments conducted in 2019-2020-2021, several mulberry varieties were simultaneously controlled; Tajikistan m/s was taken as a control. Environmental factors influenced the qualitative and quantitative indicators of the varieties in the experiment, and among the tested varieties, the Sanish-39 and Sanish-38 varieties were superior to the Tajikistan s/m variety in all their indicators. The variety Sanish-38 differed from other tested varieties in the abundance of branches and the dense arrangement of leaves on the branches. For the Sanish-39 variety, the average yield was 132 c/ha, which is +6 more than the control, especially in favorable weather, the leaf yield reached 154 c/ha. This figure was +16 c/ha compared to the Tajikistan m/s variety